Metacognitions associated with reproductive concerns: A cross-sectional study of young adult female cancer survivors in China - Xiao, Pan Pan; Ding, Si Qing; Duan, Ying Long; Luo, Xiao Fei; Zhou, Yi; Cheng, Qin Qin; Liu, Xiang Yu; Xie, Jian Fei; Cheng, Andy SK (Frontiers in Psychology, 2022)
Objective: Cancer and its treatments affect patients’ fertility potential. This study examined the prevalence of reproductive concerns and their relationship with metacognitions among Chinese young adult female cancer survivors (YAFCS). Methods: A total of 318 YAFCS (aged 18 to 39) completed an online survey from March to December 2021. Participants reported sociodemographic characteristics, reproductive concerns and metacognitions. Reproductive concerns were measured using the Reproductive Concerns after Cancer scale (RCAC), and metacognitions were measured by the Short Form of Metacognitions Questionnaire (MCQ-30). We used Pearson correlation analysis to examine associations between metacognitions and reproductive concerns across multiple domains and multivariable linear regression to determine the influencing factors of reproductive concerns. Results: The mean score of reproductive concern among YAFCS was 49.97±12.52. A total of 57.9% of participants reported a high level of concern regarding at least one dimension of reproductive concerns, and they were most concerned about their child's health and least concerned about partner disclosure of fertility status. We also found a moderate association between RCAC and MCQ-30 scores (r=0.408, P<0.001). In multivariate analyses, metacognitions, especially negative metacognitive beliefs had an impact on reproductive concerns among YAFCS (P<0.001). Conclusion: Higher reproductive concerns were associated with higher metacognitions among YAFCS, especially with negative metacognitive beliefs. Oncology professionals should pay attention to assessing reproductive concerns in patients who want to have children or who have no children. Moreover, metacognitive beliefs may be an intervention target for alleviating reproductive concerns among YAFCS.